Note of the editors - Board, Editorial (Documents d’Anàlisi Geogràfica, 2010)
Beginning in 2010, DOCUMENTS D’ANÀLISI GEOGRÀFICA (DAG) will have a new numeration system that follows the model of other scientific journals of quality. Thus, this issue is volume 56, no. 1, and corresponds to the period January-April 2010. The three annual issues that DAG publishes since 2009 (numbered 1 to 3) will constitute a single volume (with consecutive pagination). New instructions for authors and more information about the selection process and publication are included in this issue as well.